Discovery of glyantrypine‐family alkaloids as novel antiviral and antiphytopathogenic‐fungus agents. Issue 3 (25th November 2021) - Hao, Ya‐nan; Yu, Mo; Wang, Kai‐hua; Zhu, Bin‐bing; Wang, Zi‐wen; Liu, Yu‐xiu; Ma, De‐jun; Wang, Qing‐min
Abstract: BACKGROUND: Plant diseases caused by viruses and fungi have caused great losses to crop quality and yield. The discovery of novel and efficient antiviral and antiphytopathogenic‐fungus agents is urgently needed. It is the most important pesticide innovation strategy to find active compounds from natural products. Here, glyantrypine‐family alkaloids were taken as the parent structures and a series of their derivatives were designed through molecular splicing, ring expansion, and ring contraction strategies, and synthesized. The anti‐tobacco mosaic virus (TMV) activities and antifungal activities of these alkaloids were systematically investigated for the first time. RESULT: The antiviral activities of compounds 7bb, 7bc, 11c, 18b, 18d, 28d, and 28e are equivalent to or better than that of ribavirin (inhibitory rates 39%, 37%, and 40% at 500 μg mL −1 for inactivation, curative, and protection activity in vivo, respectively). Compounds 18d and 28d with good antiviral activities were selected for antiviral mode of action studies, which indicated that these alkaloids could achieve good antiviral effects by inhibiting TMV particle extension during assembly. These compounds also exhibited broad‐spectrum fungicidal activities. CONCLUSION: Glyantrypine‐family alkaloids and their derivatives were synthesized and evaluated for anti‐TMV and fungicidal activities for the first time. Compounds 18d and 28d with excellent antiviral activities and compound 7bc with remarkable fungicidal activity emerged as novel lead compounds. This study lays a foundation for the application of glyantrypine alkaloids in plant protection. Abstract : A series of glyantrypine‐family alkaloid analogues were rationally designed, synthesized, and evaluated for antiviral activities and fungicidal activities. Compounds 18d and 28d with excellent antiviral activities and compound 7bc with remarkable fungicidal activity emerged as novel lead compounds. © 2021 Society of Chemical Industry.